Komunikasi Pengungkapan Diri (Self Disclosure) Sebagai Resiliensi Mahasiswa Broken Home (Studi Fenomenologi Proses Resiliensi Mahasiswa Broken Home di Surabaya) - Buana, Daya Ning; Dewi, Putri Aisyiyah Rachma (The Commercium, 2023)
Broken Homes tend to be synonymous with an incomplete family or a family with divorced parents. Even though a family that has intact members can also be referred to as a "Broken Home family" when the relationships that are established are not harmonious and there is no warmth in them, This causes the child to experience trauma and some emotional disturbances. Children with stable emotional maturity, on the other hand, will be able to be resilient, one of which is through self-disclosure. The purpose of this study was to find out how self-disclosure communication acts as a form of resilience for Broken Home students in Surabaya. This research method is qualitative with a phenomenological approach. Data was collected through the stages of observation, in-depth interviews, and document review. The results showed that self-disclosure played a bigger role in the resilience process for female informants than for male informants. This is because female informants can take positive things from the advice and words of encouragement from their interlocutors, while male informants do not have such a big effect. Keyword : Self Disclosure, Resilience, Broken Home